Pharmacokinetics of Intranasally Administered Dexmedetomidine in Chinese Children - Wang, Cheng-Yu; Ihmsen, Harald; Hu, Zhi-Yan; Chen, Jia; Ye, Xue-Fei; Chen, Fang; Lu, Yi; Schüttler, Jürgen; Lian, Qing-Quan; Liu, Hua-Cheng (Frontiers in Pharmacology, 2019)
Background: Intranasal application is a comfortable, effective, nearly non-invasive and easy route of administration in children. To date, there is, however, only one pharmacokinetic study on intranasal dexmedetomidine in pediatric populations and none in Chinese children available. Therefore, this study aimed to characterize the pharmacokinetics of intranasal administered dexmedetomidine in Chinese children. Methods: Thirteen children aged 4-10 years undergoing surgery received 1 µg/kg dexmedetomidine intranasally. Arterial blood samples were drawn at various time points until 180 min after dose. Dexmedetomidine plasma concentrations were measured with HPLC and mass-spectrometry. Pharmacokinetic modelling was performed by population analysis using linear compartment models with first order absorption. Results: An average peak plasma concentration of 748±30 pg/mL was achieved after 49.6±7.2 min. The pharmacokinetics of dexmedetomidine was best described by a two-compartment model with first order absorption and an allometric scaling with estimates standardized to 70 kg body weight. The population estimates (SE) per 70 kg bodyweight of the apparent pharmacokinetic parameters were clearance CL/F=0.32 (0.02) L/min, central volume of distribution V1/F=34.2 (4.9) L, intercompartmental clearance Q2/F=10.0 (2.2) L/min, and peripheral volume of distribution V2/F=34.9 (2.3) L. The estimated absorption rate constant was Ka=0.038 (0.004) min-1. Conclusions: When compared to studies in Caucasians, Chinese children showed a similar time to peak plasma concentration after intranasal administration, but the achieved plasma concentrations were higher. about 3 times higher. Possible reasons are differences in age, ethnicity and mode of administration.